TRADISI MANIAN (Studi Bentuk dan Dampak Tradisi Manian dalam Perayaan Maulid Nabi Muhammad SAW di Negeri Kailolo Kabupaten Maluku Tengah) - Sanni Fitriyani Marasabessy (IAIN Ambon, 2018)
Manian is a custom and tradition or belief to set basudara done on the birthday of the Prophet Muhammad to entertain families who have been separated a long time. This study deals with how society Kailolo State did Manian tradition in celebration of the birthday of the Prophet Muhammad, and their impact to the community what Kailolo State. This study is based on the perspective of structural functionalism and symbols with research methods in-depth interviews and participant observation to collect data in the field. Based on interviews and observations of researchers regarding the form and impact of these traditions, researchers produced several findings in the field. Manian tradition performed by the State society Kailolo an association basudara suda tradition existed since ancient times until now and have very many functions in various ways. This is proven by the friendship between communities that never severed. As for the celebration of tradition Manian, are generally the same except that there is a difference between Highways Marasabessy. Manian are celebrated by Marasabessy clan was divided into two, namely Manian Hala Totui or food bodies and Manian Flower Candle or flower luck